1998
DOI: 10.1002/(sici)1096-8628(19980605)77:5<345::aid-ajmg1>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Teebi hypertelorism syndrome with Tetralogy of Fallot

Abstract: A 34-month-old boy presented with clinical manifestations of Teebi hypertelorism syndrome including prominent forehead with frontal bossing, hypertelorism, exophthalmos due to shallow orbits, a short and broad nose with anteverted nares, small hands and feet with interdigital webbing, umbilical hernia, and shawl scrotum. In addition, he had previously undescribed manifestations including tetralogy of Fallot, bilateral inguinal testes, and bifid scrotum. His phenotypically normal mother showed splayed labiae ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…There have been multiple reports of patients with Teebi hypertelorism syndrome in the literature without a molecular etiology since it was first described in 1987 in a large Kuwaiti kindred with 16 affected individuals in four generations [Teebi, ]. We reviewed the 22 individuals in 12 families who were well characterized in the literature and identified shared features with our patients including hypertelorism, umbilical malformations including omphalocele, shawl scrotum, natal teeth, preauricular pits, and craniosynostosis (Table ) [Teebi, ; Stratton, ; Toriello and Delp, ; Tsukahara et al, ; Nakagawa et al, ; Tsai et al, ; Koenig, ; Machado‐Paula and Guion‐Almeida, ; Han et al, ]. Therefore, we feel that it is possible that a significant proportion of additional Teebi hypertelorism syndrome patients may also harbor mutations in SPECC1L .…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple reports of patients with Teebi hypertelorism syndrome in the literature without a molecular etiology since it was first described in 1987 in a large Kuwaiti kindred with 16 affected individuals in four generations [Teebi, ]. We reviewed the 22 individuals in 12 families who were well characterized in the literature and identified shared features with our patients including hypertelorism, umbilical malformations including omphalocele, shawl scrotum, natal teeth, preauricular pits, and craniosynostosis (Table ) [Teebi, ; Stratton, ; Toriello and Delp, ; Tsukahara et al, ; Nakagawa et al, ; Tsai et al, ; Koenig, ; Machado‐Paula and Guion‐Almeida, ; Han et al, ]. Therefore, we feel that it is possible that a significant proportion of additional Teebi hypertelorism syndrome patients may also harbor mutations in SPECC1L .…”
Section: Discussionmentioning
confidence: 99%
“…THS is rare and only 36 affected individuals from 9 families have been reported prior to this family. Among these 36 patients, the clinical findings in 18 patients have been well documented and we have summarized the data from these individuals and the proposita in Table I to make a total of 19 patients [Teebi, 1987 (6 patients); Stratton, 1991; Toriello and Delp, 1994 (2 patients); Tsukahara et al, 1995; Nakagawa et al, 1998; Tsai et al, 2002 (3 patients); Koenig, 2003 (2 patients); Machado‐Paula and Guion‐Almeida, 2003 (2 patients)].…”
Section: Discussionmentioning
confidence: 99%
“…One other child with THS was diagnosed with atrial flutter but an echocardiogram in that child also showed a large secundum atrial septal defect (ASD) and a patent ductus arteriosus [Tsai et al, 2002]. Other cardiac anomalies have included mitral valve prolapse and a cardiac murmur, respectively, in a mother and her daughter [Toriello and Delp, 1994], a ventriculoseptal defect [Tsukahara et al, 1995], and tetralogy of Fallot [Nakagawa et al, 1998]. Based upon these five patients with structural cardiac defects, congenital heart defects should be considered in any THS patient with a murmur and a cardiology evaluation with EKG and echocardiogram should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, structural cardiac anomalies are seen in 14% of the cases. For instance, tetralogy of Fallot has recently been reported by Nakagawa et al 5 Anomalies such as isolated atrial septal defect are also seen in some patients. Patent ductus arteriosus has also been reported by Tsai et al 6 Intra-abdominal abnormalities are common in patients with THTS.…”
mentioning
confidence: 96%